PWE-088a Should Meals Be Blocked During Ambulatory pH Monitoring?. (17th August 2016) - Athanasakos, E; Harrington, S; Neilan, L; Raeburn, A; Zarate, N; Emmanuel, A; Sweis, R
Abstract : Introduction: The pH sensor cannot differentiate retrograde from anterograde bolus movement. Physiologists often block meals in pH studies to reduce the artefact of acid-containing food/fluids; however there is no clear evidence with regards to the appropriateness of this practice. The aim of this study was to compare results of ambulatory pH monitoring without and with meals blocked in patients being investigated for reflux symptoms. Methods: Standard pH parameters were compared without and with meals blocked in consecutive patients presenting to University College London Hospital Oesophageal Unit, a tertiary referral centre. T-test was used for quantitative and chi-square for qualitative variables. Results are presented as mean±standard deviation(SD) Results: pH studies for 99 patients with reflux-like symptoms were collected prospectively over 3 months. Under 17 hour recordings (n = 2) or studies ON acid-reducing therapy (n = 6) were excluded. Mean age of the 91 remaining patients (M31:F60) was 50±15 years. Time spent without and with meals blocked was 1388±100 and 1243±114 minutes respectively (p < 0.001); 145±111 min difference. There was no difference in the quantitative or qualitative Total reflux (% time pH < 4; TR), Upright reflux (UR) or Supine Reflux (SR) when analysed without and with meals excluded.(Table ) At individual level, meal exclusion changed TR/UR/SR to become negative in 4 and positive in 2 patients; average 5% (range 2.5–23 min) of the mealtime was taken up swallowing acid-containing products. Food diary occasionally provided guidance, although quality of self-reports was widely variable. There was no difference in qualitative (p = 0.538) or quantitative (p = 0.338) Symptom Index (SI) when meals were not blocked (12 positive; mean 16.9±22.6%) compared to when meals were blocked (16 positive; mean 18.4±25.4%). Also there was no difference in any pH parameters between the two groups with all symptoms pooled, or with typical (heartburn, regurgitation, chest pain; n = 59) and atypical symptoms (laryngopharyngeal reflux, cough, belch, dysphagia; n = 33) analysed separately (p = NS for all). Furthermore there was no difference in any pH parameter when results were analysed with (n = 43) or without (n = 48) a hiatus hernia (p = NS for all). Conclusion: In 93% of patients, routine blocking of meals had no impact on the final report. In a small minority, the artefact of swallowing acidic products as well as shortening of the 24 hour study to exclude meals (average ≥2 hours) can also change results from positive to negative and vice versa. Disclosure of Interest: None Declared